1988
DOI: 10.1002/food.19880320903
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interesterified dietary fat mixtures on various lipid indices and liver metal content of rats in fat‐metabolism disturbance

Abstract: Adult male and female Wistar rats were fed isoenergetically for a 6 week period with a lipogenic diet containing a 20% fat mixture which caused fat-metabolism disturbance. One group consumed the mixture of sunflower oil and lard in a ratio of 0.91 P/S, the other group the interesterified form of the same mixture. The linoleic acid content of the mixtures was 0.4%. The fat mixture of the third group's diet was adjusted with soya oil to a linoleic-acid content of 0.8%. The results were compared to the control da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

1989
1989
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
1
Order By: Relevance
“…With the technological change, namely with the interesterification of only one component (the lard) in the fat mixture, we obtained a more favourable effect than in our former experiments [7] when the whole fat-mixture was interesterified. Similar, or in some cases even more favourable lipid levels were found as an effect of the partial interesterification than with the noninteresterified fat mixture.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…With the technological change, namely with the interesterification of only one component (the lard) in the fat mixture, we obtained a more favourable effect than in our former experiments [7] when the whole fat-mixture was interesterified. Similar, or in some cases even more favourable lipid levels were found as an effect of the partial interesterification than with the noninteresterified fat mixture.…”
Section: Discussioncontrasting
confidence: 47%
“…According to our earlier results obtained in experiments modelling disturbances of fat metabolism [7], a diet with an interesterified 20 % fat mixture (containing lard: sunflower oil = 65 : 35) increased in a higher degree the total lipids, triglyceride and total cholesterol contents of the liver than a fat mixture of similar composition without interesterification. We suggested that this phenomenon was due to the fact that the fatty acid regroupings in the triglyceride structure developed in both of the fats, and from the biological point of view their "random" distribution was unfavourable.…”
mentioning
confidence: 83%